Q: What is the answer to -9p plus 6p equals?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

algebra8p +4 = 10 +6p+8p - 6p = +10 - 42p = 6p = 3

9p + 27 = 9(p + 3)

14 + 6p = 6 + 7p 8 = p

First get all the p variables on one side of the equation by subtracting 6p from both sides. Giving you 3p + 14 = 23 Now subtract 14 from both sides. 3p = 9 Finally divide both sides by 3. p = 3

Evaluate 9p + 33 for p = 5

Related questions

3p + 6p = (3 + 6)p = 9p

14p + 14q + p - 7q - 6p = 9p + 7q

12x+15p-6p+11x = 12x+11x+15p-6p = (12+11)x+(15-6)p = 23x + 9p

algebra8p +4 = 10 +6p+8p - 6p = +10 - 42p = 6p = 3

9p + 27 = 9(p + 3)

14 + 6p = 6 + 7p 8 = p

p2 + 9p + 18/ p + 6(p + 6)(p + 3)/ p + 6(p + 6)(p + 3)/ p + 6p + 3

First get all the p variables on one side of the equation by subtracting 6p from both sides. Giving you 3p + 14 = 23 Now subtract 14 from both sides. 3p = 9 Finally divide both sides by 3. p = 3

Evaluate 9p + 33 for p = 5

p=1125

17 + 6p = 9 6p = -8 p = -8/6 p = -4/3

p = 4